Perovskite quantum dot and polymer powder and preparation method and application thereof
By combining spray and photocuring, perovskite quantum dots are fixed in the polymer, solving the problem of poor long-term stability of perovskite quantum dots, and achieving efficient dense coating and stability improvement of the material.
Patent Information
- Application Number
- CN202311431746.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
Perovskite quantum dots have poor long-term stability in actual application, and factors such as water, oxygen, high temperature, and high energy radiation in the external environment are likely to destroy their structure.
The perovskite precursor, ligand, polymer monomer, initiator and solvent are mixed to form micron-scale spray droplets, and the perovskite quantum dots are fixed in the polymer through photocuring reaction, preventing their interlayer movement and achieving dense coating.
It significantly improves the long-term stability of perovskite quantum dots, prevents them from moving between layers and structural damage within the polymer, and improves the water and oxygen resistance of the material.
Smart Images

Figure CN119912624A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photoluminescent materials and relates to a perovskite quantum dot@polymer powder and a preparation method and application thereof. Background Art
[0002] As a new type of semiconductor light-emitting material, perovskite quantum dots have excellent photoelectric properties such as high quantum yield, narrow half-peak width, and adjustable light emission. In addition, the preparation process of perovskite quantum dots is very simple, and perovskite quantum dots can be prepared at room temperature or low temperature. At the same time, perovskite quantum dots can also increase the display color gamut to more than 100% NTSC.
[0003] CN107286930A discloses a method for preparing perovskite quantum dot nanorods from methylamine lead bromide perovskite quantum dots. The method comprises the following steps: first, cleaning a glass slide, first pouring a piranha solution (concentrated sulfuric acid and 30% hydrogen peroxide in a ratio of 7:3) and boiling for 30 minutes, then pouring an ethanol solution and a deionized water solution in turn, each ultrasonically cleaning for 15-30 minutes, taking out and drying with nitrogen; second, dissolving a dimethylformamide (DMF) solution of methylamine lead bromide perovskite quantum dots in toluene to prepare a 1×10 -4 -1ⅹ10 -3 mol / L methylamine lead bromine perovskite quantum dot toluene solution; step three, drop the methylamine lead bromine perovskite quantum dot toluene solution on the glass slide in the culture dish; step four, cover the culture dish, and then wait for the methylamine lead bromine perovskite quantum dot toluene solution to dry at room temperature to obtain perovskite quantum dot nanorods.
[0004] However, the long-term stability of perovskite quantum dots in practical applications is a challenging issue. Water, oxygen, high temperature, high-energy radiation, etc. in the external environment will destroy the structure of perovskite quantum dots. Therefore, it is urgent to improve the stability of perovskite quantum dot materials.
[0005] On the one hand, the prior art improves the water and oxygen barrier properties of the packaging material, and improves the protection of quantum dots through the barrier properties of external glue. For example, CN116694293A discloses a UV glue, a perovskite quantum dot glue solution, and a perovskite quantum dot packaging structure, in which the perovskite quantum dots are directly dispersed in the glue for encapsulation. However, in the process of quantum dots being dispersed in the glue, their surface ligands are easily detached, and the interaction between the glue and the quantum dots will affect the performance of the quantum dots. On the other hand, some researchers have used polymers to encapsulate quantum dots, but because the polymer molecules are large, they cannot be densely coated, and it is difficult to prevent the quantum dots from agglomerating between the layers inside the polymer.
[0006] Therefore, how to improve the long-term stability of perovskite quantum dots is a technical problem that needs to be solved urgently. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a perovskite quantum dot@polymer powder and its preparation method and use. The present invention adopts a combination of spraying and photocuring, so that one end of the ligand is coordinated with the perovskite quantum dot and the other end is combined with the polymer monomer to form a double bond addition anchor, thereby fixing the position of the perovskite quantum dot in the polymer and preventing the interlayer movement of the perovskite quantum dot in the polymer; achieving dense coating on the surface of the polymer perovskite quantum dot, obtaining a powdered material, thereby improving the long-term stability of the perovskite quantum dot.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, a method for preparing perovskite quantum dots@polymer powder comprises the following steps:
[0010] The perovskite precursor, ligand, polymer monomer, initiator and solvent are mixed to obtain a reaction solution, the reaction solution is sprayed to obtain spray droplets, and the spray droplets are subjected to a photocuring reaction to obtain the perovskite quantum dot@polymer powder.
[0011] The present invention adopts a method combining spraying and photocuring. The reaction liquid is first formed into micron-sized spray droplets by spraying. When the spray droplets enter the photocuring reaction stage, as the droplets solidify and the solvent evaporates, the perovskite quantum dots crystallize and grow inside the droplets. During the growth process, the ligands coordinate with the quantum dots to prevent the perovskite quantum dots from moving between layers in the polymer. Through the connecting effect of the ligands, the dense coating of the surface of the polymer perovskite quantum dots is achieved, thereby improving the long-term stability of the perovskite quantum dots.
[0012] In the present invention, if the reaction liquid is directly subjected to a photocuring reaction without first forming droplets by spraying, the monomer cannot be rapidly polymerized to form a powder solid, and thus the rapid precipitation of quantum dots cannot be solved; and if the reaction is directly sprayed, quantum dot solid powder cannot be obtained; at the same time, if the reaction liquid does not contain a ligand, stable quantum dots cannot be obtained. That is, in the present invention, the spraying, photocuring and raw materials of the reaction liquid must exist at the same time and cooperate with each other to achieve the purpose of tightly encapsulating the perovskite quantum dots with the polymer.
[0013] Preferably, the perovskite precursor includes A-site ions, B-site ions and C-site ions; the A-site ions include any one of cesium ions, methylammonium ions, formamidine ions, lithium ions, sodium ions, potassium ions or rubidium ions, or a combination of at least two of them; the B-site ions include any one of lead ions, strontium ions, calcium ions, barium ions, manganese ions, rare earth ions, bismuth ions, silver ions, indium ions, copper ions or nickel ions, or a combination of at least two of them; the C-site ions include any one of halogen ions, or a combination of at least two of them.
[0014] Preferably, the perovskite precursor comprises a halide containing an A-site ion and a halide containing a B-site ion.
[0015] Preferably, the polymerizable monomers include a first polymerizable monomer and / or a second polymerizable monomer.
[0016] The first polymer monomer is a monofunctional monomer, and the first polymer is linked to the surface of the quantum dot through a monofunctional group; the second polymer monomer is a multifunctional monomer, which contains at least two unsaturated functional groups, and different types of unsaturated functional groups are not in the same plane, and several of the multifunctional monomers can be polymerized to form a three-dimensional structure.
[0017] The first polymer monomer provided by the present invention, when it is a single functional group, serves as a filler and has a chain structure after polymerization. As a filler, it can reduce the interlayer movement of quantum dots and maintain the toughness of the material.
[0018] The second polymer monomer provided by the present invention contains more than one type of unsaturated functional groups, and the different types of unsaturated functional groups are not in the same plane (not on the same branch chain). Several of the multifunctional monomers can be polymerized with each other to form a three-dimensional structure, which is more conducive to fixing the position of the perovskite quantum dots in the polymer and preventing the interlayer movement of the perovskite quantum dots in the polymer. Through the connection effect of the ligand, dense coating of the surface of the polymer perovskite quantum dots is achieved, thereby improving the long-term stability of the perovskite quantum dots.
[0019] In the present invention, the first polymer monomer and the second polymer monomer are added at the same time, which is more conducive to achieving dense coating on the surface of the polymer perovskite quantum dots. At the same time, part of the chain body of the first polymer monomer can be located inside the three-dimensional coating shell formed by the polymer, which can not only increase the density of the coating shell, but also play a filling role, reduce the interlayer movement of the quantum dots, thereby improving the long-term stability of the perovskite quantum dots.
[0020] Preferably, the ligand comprises a first ligand and / or a second ligand.
[0021] The first ligand comprises a modified functional group, and the modified functional group is coordinated to a defect vacancy of a perovskite quantum dot; the second ligand comprises at least two anchoring functional groups, and one of the anchoring functional groups is bonded to the perovskite quantum dot, and the other anchoring functional group is bonded to the first polymer monomer or the second polymer monomer.
[0022] In the present invention, when the second ligand contains at least two anchoring functional groups, the interlayer movement of the perovskite quantum dots in the polymer is prevented, and the dense coating of the surface of the polymer perovskite quantum dots is achieved through the connecting effect of the ligand, thereby improving the long-term stability of the perovskite quantum dots.
[0023] The ligand material provided by the present invention can be combined with polymer monomers on the one hand, and can also be coordinated with perovskite quantum dots on the other hand. Therefore, through the coordinated cooperation of the first ligand and the second ligand, the perovskite quantum dots are protected from both physical and chemical perspectives.
[0024] Preferably, the first polymerizable monomer comprises methyl acrylate.
[0025] Preferably, the second polymer monomer includes any one of acrylic acid, acrylic acid ester, perfluorodecene or vinyl pyrrolidone, or a combination of at least two thereof.
[0026] In the present invention, methyl acrylate includes but is not limited to methyl methacrylate (MMA); acrylate includes but is not limited to triethylene glycol dimethacrylate (TEDGMA), isobornyl acrylate (IBOA), tripropylene glycol diacrylate (TPGDA), diethylene glycol diacrylate (DEGDA), neopentyl glycol diacrylate (NPGDA), trimethylolpropane triacrylate (TMPTA) or pentaerythritol triacrylate (PETA) and the like; the acrylic acid includes but is not limited to hexanediol diacrylate (HDDA) and the like.
[0027] Preferably, the first ligand comprises any one or a combination of at least two of oleylamine, oleic acid, octylamine, octanoic acid, dodecylbenzenesulfonic acid, didodecylammonium bromide, oleylamine chloride, octylamine bromide, oleylamine bromide or iodized oleylamine.
[0028] Preferably, the second ligand includes any one of hexanedithiol, 3,3'-thiodipropionic acid, trimethylolpropane tris(3-mercaptopropionate) or pentaerythritol tetrakis(3-mercaptopropionate) or a combination of at least two thereof.
[0029] Preferably, the initiator comprises a photoinitiator and / or a thermal initiator.
[0030] In the present invention, the photoinitiator and the thermal initiator are both selected according to conventional techniques. The photoinitiator includes but is not limited to 1173 photoinitiator, 184 photoinitiator or 2959 photoinitiator, etc., and the thermal initiator includes but is not limited to azobisisobutyronitrile, azobisisoheptanenitrile, etc.
[0031] Preferably, the molar ratio of the B-site ion in the perovskite precursor to the ligand is 1:(0.1-2), for example, 1:0.1, 1:0.3, 1:0.5, 1:0.8, 1:1, 1:1.3, 1:1.5, 1:1.8 or 1:2, etc.
[0032] In the present invention, the molar ratio of the B-site ion to the ligand, wherein the ligand is the total molar amount of all ligands; if both the first ligand and the second ligand are included, the specific molar ratio of the two can be adaptively adjusted according to the specific types.
[0033] Preferably, the molar ratio of the B-site ions in the perovskite precursor to the polymer monomer is 1:(10-50), for example, 1:10, 1:15, 1:20, 1:25, 1:30, 1:40 or 1:50, etc.
[0034] In the present invention, the molar ratio of the B-site ion to the polymer monomer, wherein the polymer monomer is the total molar ratio of all polymer monomers.
[0035] Preferably, in the perovskite precursor, the molar ratio of B site ions to A site ions is 1:(0.5-2), for example, 1:0.5, 1:1, 1:1.5 or 1:2, the molar ratio of B site ions to C site ions is 1:(0.5-10), the molar ratio of B site ions to C site ions is 1:(0.5-10), for example, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9 or 1:10, etc.
[0036] Preferably, the volume of the solvent corresponding to 1 g of polymer monomer is 0.5 to 500 mL, for example 0.5 mL, 1 mL, 5 mL, 10 mL, 50 mL, 100 mL, 150 mL, 200 mL, 250 mL, 300 mL, 350 mL, 400 mL, 450 mL or 500 mL, etc.
[0037] Preferably, the reaction solution also includes an antioxidant.
[0038] Preferably, the molar ratio of the B-site ions in the perovskite precursor to the antioxidant is 1:(0.1-1), such as 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9 or 1:1, etc. Preferably, the spray carrier gas in the spraying process includes a protective gas.
[0039] Preferably, the temperature of the spray carrier gas during the spraying process is 50-120°C.
[0040] In the present invention, during the spraying process, the spray carrier gas (i.e., the spray treatment of the reaction liquid is achieved through the carrier gas) carries the spray droplets in the reaction chamber for the photocuring reaction during the spraying process to carry out the photocuring reaction; if the temperature of the spray carrier gas is too low, below 50°C, the crystallization of quantum dots cannot be achieved; and if the temperature is too high, above 120°C, it may cause the formed quantum dots to further decompose.
[0041] Preferably, the light source in the photocuring reaction includes ultraviolet light or blue light.
[0042] Preferably, the curing power during the photocuring reaction is 50 to 20000 mW / cm 2 .
[0043] Preferably, after the photocuring reaction, a heating and drying treatment is performed under the same light source.
[0044] In the present invention, after the photocuring reaction, the heating and drying process is continued under the same light source, so that the obtained product structure is a polymer-coated perovskite quantum dot powder; if only the photocuring reaction process is carried out, the obtained perovskite quantum dots will have the problem of incomplete solvent evaporation, resulting in a decrease in the stability of the polymer-coated perovskite quantum dot powder, and even difficulty in forming perovskite quantum dots.
[0045] Preferably, the heating and drying temperature is 80-120°C.
[0046] In the present invention, the temperature of heating and drying is higher than the temperature of the spray droplets carried by the carrier gas during the photocuring process, which further improves the crystallization quality of the quantum dots; and if the temperature is too low, below 80°C, it is not conducive to improving the crystallization quality of the quantum dots, thereby causing a decrease in stability.
[0047] As a preferred technical solution, the preparation method comprises the following steps:
[0048] The perovskite precursor, ligand, polymer monomer, initiator and solvent are mixed to obtain a reaction solution, and the reaction solution is sprayed to obtain spray droplets. The temperature of the spray carrier gas during the spraying process is 50 to 120° C. The spray droplets are sprayed at 50 to 20000 mW / cm 2The curing power is used to perform a photocuring reaction. After the photocuring reaction, a heating and drying treatment is performed at a temperature of 80 to 120° C. under the same light source to obtain the perovskite quantum dot@polymer powder.
[0049] It should be noted that the present invention has no special requirements on the sources of the raw materials, and they can be obtained through commercial channels or prepared by themselves. When prepared by themselves, they are all conventional technical means that can be directly known to those skilled in the art.
[0050] In a second aspect, the present invention provides a perovskite quantum dot@polymer powder, wherein the perovskite quantum dot@polymer powder is prepared by the preparation method described in the first aspect; in the perovskite quantum dot@polymer powder, a polymer is coated on the surface of the perovskite quantum dot; a plurality of the polymer monomers are polymerized to form a plurality of coating cages with three-dimensional shell structures, and the coating cages coat the perovskite quantum dot;
[0051] The ligand contains at least two groups of functional groups, one group of which is bonded to the inner wall of the coating cage, and the other group of which is bonded to the perovskite quantum dots; the perovskite quantum dots are anchored in the coating cage through the ligand.
[0052] In a third aspect, the present invention further provides a use of the perovskite quantum dot@polymer powder as described in the second aspect, wherein the use comprises using the perovskite quantum dot@polymer powder in a display device.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] The present invention adopts a method combining spraying and photocuring. The reaction liquid is first formed into micron-sized spray droplets by spraying. When the spray droplets enter the photocuring reaction stage, as the droplets solidify and the solvent evaporates, the perovskite quantum dots crystallize and grow inside the droplets. During the growth process, the ligands coordinate with the quantum dots to prevent the perovskite quantum dots from moving between layers in the polymer. Through the connecting effect of the ligands, the dense coating of the surface of the polymer perovskite quantum dots is achieved, thereby improving the long-term stability of the perovskite quantum dots. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 This is a schematic diagram of the preparation process provided in Example 1.
[0056] Figure 2 A comparison chart of the wet-heat stability of perovskite quantum dots provided in Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION
[0057] The technical solution of the present invention is further described below by specific implementation methods. Those skilled in the art should understand that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. In addition, the terms "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. Thus, features defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, the meaning of "multiple" is two or more.
[0058] Example 1
[0059] This embodiment provides a MAPbBr3@polymer quantum dot green light powder, in which the polymer is coated on the surface of the perovskite quantum dot MAPbBr3.
[0060] The preparation method is as follows:
[0061] (1) MABr, PbBr2, octylamine bromide (first ligand), hexanedithiol (second ligand), phosphite (antioxidant), MMA (first monomer), and TEDGMA (second monomer) were weighed in a molar ratio of 1:1:0.4:0.2:0.2:20:20, and then dissolved in N,N-dimethylformamide (DMF), wherein the corresponding relationship of MMA+TEDGMA:DMF is 10 g:20 ml. After the above solution is stirred evenly, a photoinitiator 1173 is added and stirred evenly to form a reaction solution;
[0062] (2) Figure 1 As shown, the reaction liquid is sprayed through a nozzle using a spray carrier gas (nitrogen) to form micron-sized spray droplets, and the spray droplets are sprayed into a reaction chamber. The liquid inlet rate is 500 ml / h, and the temperature of the spray carrier gas is 75°C. In the reaction chamber, a photocuring reaction is first performed under ultraviolet light, and the ultraviolet light (365 nm) curing power is 600 mW / cm 2 After the photocuring reaction, the reactants are dried at 80° C. under the same light source to obtain the perovskite quantum dot@polymer powder.
[0063] Example 2
[0064] This embodiment provides a MAPbBrI2@polymer quantum dot red light powder, in which a polymer is coated on the surface of the perovskite quantum dot MAPbBrI2.
[0065] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, MABr, PbI2, octylamine iodide, hexanedithiol, phosphite, MMA, and TEDGMA are weighed in a molar ratio of 1:1:0.4:0.2:0.2:20:20.
[0066] The rest of the preparation methods and parameters were the same as those in Example 1.
[0067] Example 3
[0068] This embodiment provides a MAPbBrCl2@polymer quantum dot blue light powder, in which a polymer is coated on the surface of the perovskite quantum dot MAPbBrCl2.
[0069] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, MABr, PbCl2, octylamine bromide, octylamine chloride, hexanedithiol, phosphite, MMA, and TEDGMA are weighed in a molar ratio of 1:1:0.13:0.27:0.2:0.02:20:20.
[0070] The rest of the preparation methods and parameters were the same as those in Example 1.
[0071] Example 4
[0072] This embodiment provides a CsPbBr3@polymer quantum dot green light powder, in which the polymer is coated on the surface of the perovskite quantum dot CsPbBr3.
[0073] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, CsBr, PbBr2, octylamine bromide, hexanedithiol (ligand), phosphite, MMA, and TEDGMA are weighed in a molar ratio of 1:1:0.4:0.2:0.2:20:20.
[0074] The rest of the preparation methods and parameters were the same as those in Example 1.
[0075] Example 5
[0076] This embodiment provides a MAPbBr2I@polymer quantum dot yellow light powder, in which a polymer is coated on the surface of the perovskite quantum dot MAPbBr2I.
[0077] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, MAI, PbBr2, octylamine bromide, octylamine iodide, hexanedithiol, phosphite, MMA, and TEDGMA are weighed in a molar ratio of 1:1:0.2:0.2:0.2:0.2:20:20.
[0078] The rest of the preparation methods and parameters were the same as those in Example 1.
[0079] Example 6
[0080] This embodiment provides a hydrophilic MAPbBr3@polymer quantum dot green light powder, in which the polymer is coated on the surface of the perovskite quantum dot MAPbBr3.
[0081] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, MABr, PbCl2, octylamine bromide, AA, phosphite, MMA, and TEDGMA are weighed in a molar ratio of 1:1:0.4:2:0.2:18:20.
[0082] The rest of the preparation methods and parameters were the same as those in Example 1.
[0083] Example 7
[0084] This embodiment provides a hydrophobic MAPbBr3@polymer quantum dot green light powder, in which the polymer is coated on the surface of the perovskite quantum dot MAPbBr3.
[0085] The difference between this embodiment and embodiment 1 is that in step (1) of this embodiment, MABr, PbCl2, octylamine bromide, perfluorodecene, phosphite, MMA, and TEDGMA are weighed in a molar ratio of 1:1:0.4:2:0.2:18:20.
[0086] The rest of the preparation methods and parameters were the same as those in Example 1.
[0087] Example 8
[0088] The difference between this embodiment and embodiment 1 is that the second ligand hexanedithiol is not added in step (1) of this embodiment.
[0089] The rest of the preparation methods and parameters were the same as those in Example 1.
[0090] Example 9
[0091] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the temperature of the spray carrier gas is 50° C., and the drying temperature after the photocuring reaction is 100° C.
[0092] The rest of the preparation methods and parameters were the same as those in Example 1.
[0093] Example 10
[0094] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the temperature of the spray carrier gas is 120° C., and the drying temperature after the photocuring reaction is 120° C.
[0095] The rest of the preparation methods and parameters were the same as those in Example 1.
[0096] Embodiment 11
[0097] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the temperature of the spray carrier gas is 30°C.
[0098] The rest of the preparation methods and parameters were the same as those in Example 1.
[0099] Example 12
[0100] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the temperature of the spray carrier gas is 150°C.
[0101] The rest of the preparation methods and parameters were the same as those in Example 1.
[0102] Embodiment 13
[0103] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, after the photocuring reaction, no drying process is performed.
[0104] The rest of the preparation methods and parameters were the same as those in Example 1.
[0105] Embodiment 14
[0106] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, after the photocuring reaction is carried out, the drying temperature is 50°C.
[0107] The rest of the preparation methods and parameters were the same as those in Example 1.
[0108] Comparative Example 1
[0109] The difference between this comparative example and Example 1 is that in the preparation process of this comparative example, no polymer monomer is added, that is, pure perovskite quantum dots are obtained.
[0110] In step (1), MABr, PbBr2 and octylamine bromide are weighed in a molar ratio of 1:1:0.4.
[0111] The rest of the preparation methods and parameters were the same as those in Example 1.
[0112] Comparative Example 2
[0113] The difference between this comparative example and Example 1 is that in the preparation process of this comparative example, the polymer monomer is replaced by the polymer PMMA.
[0114] In step (1), MABr, PbBr2, octylamine bromide and PMMA are weighed in a molar ratio of 1:1:0.4::40.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Comparative Example 3
[0117] The difference between this comparative example and Example 1 is that in the preparation process of this comparative example, no spraying process is performed, and the reaction liquid is directly subjected to a photocuring reaction.
[0118] The rest of the preparation methods and parameters were the same as those in Example 1.
[0119] Comparative Example 4
[0120] The difference between this comparative example and Example 1 is that no ligand is added during the preparation process of this comparative example.
[0121] The rest of the preparation methods and parameters were the same as those in Example 1.
[0122] The perovskite quantum dots@polymer material (or pure perovskite quantum dots) provided in Examples 1-14 and Comparative Examples 1-4 were uniformly mixed with a photocurable resin at a mass ratio of 1:40, degassed using a vacuum degassing machine, and then coated on a barrier film with a thickness of 150 μm. The film was cured for 1 min with a 150W, 365nm UV lamp to obtain a test film. The film was aged in a constant temperature and humidity chamber at a humidity of 95 and a temperature of 65°C. The test results are shown in Table 1.
[0123] Figure 2 A comparison of the wet heat stability of the perovskite quantum dots provided by Example 1, Comparative Example 1 and Comparative Example 2 is shown. Figure 2 It can be seen that without adding polymer monomers, it is impossible to isolate the water sample from a physical point of view and improve the wet-heat stability of perovskite quantum dots. The use of dual polymer monomers can not only maintain the physical properties of the composite material but also improve the stability of the quantum dots.
[0124] Table 1 also shows the emission peak, quantum yield and half-peak width of the quantum dots; the test method of steady-state spectrum and quantum yield: using Edinburgh FLS1000 steady-state transient fluorescence spectrometer with integrating sphere accessory, excitation light wavelength: 365nm.
[0125] Table 1
[0126]
[0127]
[0128] From the data results of Examples 1-7, it can be seen that the preparation method provided by the present invention is applicable to various types of perovskite quantum dot structures, and can improve their long-term stability to obtain a product structure with high quantum efficiency and good stability.
[0129] It can be seen from the data results of Example 1 and Example 8 that when the ligand does not contain the second ligand, the perovskite quantum dots cannot be anchored, resulting in a decrease in the stability of the perovskite quantum dots after aging.
[0130] From the data results of Examples 1 and 9-12, it can be seen that when the temperature of the spray carrier gas is in the range of 50-120°C, the solvent volatilization can be achieved better; when the temperature is lower than 50°C, the solvent volatilization rate will be affected, and when the temperature is higher than 120°C, it is not conducive to the crystallization of perovskite quantum dots.
[0131] It can be seen from the data results of Example 1 and Example 13 that if the heating and drying process is not performed after the photocuring reaction, problems such as solvent residue and incomplete crystallization of quantum dots are likely to occur, resulting in low photoluminescence efficiency of quantum dots.
[0132] It can be seen from the data results of Example 1 and Example 14 that during the heating and drying process, if the temperature is too low, below 80° C., the solvent will not evaporate and the monomer polymer will not solidify, thereby causing the stability of the perovskite quantum dots to decrease.
[0133] From the data results of Example 1 and Comparative Examples 1-4, it can be seen that in Comparative Example 1, there is a lack of monomers, which cannot form a polymerized shell structure, lacks protection for quantum dots, and has poor anti-water and oxygen and anti-aging properties; in Comparative Example 2, there is a lack of monomers, but the polymer PMMA is directly added, which is difficult to achieve the effect of first polymerizing and then coating the quantum dots, and there is no effect of anchoring the quantum dots, and its performance is also poor; in Comparative Example 3, there is no spraying and direct photocuring, and due to the serious aggregation of quantum dots, the quantum yield is low, and it is difficult for the monomer polymerization to completely coat the quantum dots, and its anti-aging performance is also poor. In Comparative Example 4, no ligand is added, which greatly reduces the quantum yield. In the present invention, only through the coordinated cooperation of spraying, photocuring and the raw materials of the reaction solution can the powder product structure of the polymer tightly coating the perovskite quantum dots be obtained, thereby improving the long-term stability of the quantum dots.
[0134] In summary, the present invention adopts a method combining spraying and photocuring. The reaction liquid is first formed into micron-sized spray droplets by spraying. When the spray droplets enter the photocuring reaction stage, as the droplets solidify and the solvent evaporates, the perovskite quantum dots crystallize and grow inside the droplets. During the growth process, one end of the ligand is coordinated with the perovskite quantum dots and the other end is combined with the polymer monomer to form a double bond addition anchor, thereby fixing the position of the perovskite quantum dots in the polymer and preventing the interlayer movement of the perovskite quantum dots in the polymer. Through the connecting effect of the ligand, the dense coating of the surface of the polymer perovskite quantum dots is achieved, thereby improving the long-term stability of the perovskite quantum dots; that is, only through the coordinated cooperation of spraying, photocuring and the raw materials of the reaction liquid can the present invention obtain a powder product structure in which the polymer tightly coats the perovskite quantum dots, thereby improving the long-term stability of the quantum dots.
[0135] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing perovskite quantum dots@polymer powder, characterized in that: The preparation method comprises the following steps: The perovskite precursor, ligand, polymer monomer, initiator and solvent are mixed to obtain a reaction solution, the reaction solution is sprayed to obtain spray droplets, and the spray droplets are subjected to a photocuring reaction to obtain the perovskite quantum dot@polymer powder.
2. The method for preparing perovskite quantum dots@polymer powder according to claim 1, characterized in that: The perovskite precursor includes A-site ions, B-site ions and C-site ions; The A-site ion includes any one or a combination of at least two of cesium ion, methylammonium ion, formamidine ion, lithium ion, sodium ion, potassium ion or rubidium ion; The B-site ions include any one of lead ions, strontium ions, calcium ions, barium ions, manganese ions, rare earth ions, bismuth ions, silver ions, indium ions, copper ions or nickel ions, or a combination of at least two thereof; The C-site ions include any one or a combination of at least two of the halogen ions; Preferably, the perovskite precursor comprises a halide containing an A-site ion and a halide containing a B-site ion.
3. The method for preparing perovskite quantum dots@polymer powder according to claim 1 or 2, characterized in that: The polymer monomers include a first polymer monomer and / or a second polymer monomer; The first polymer monomer is a monofunctional monomer, and the first polymer is linked to the surface of the quantum dot through a monofunctional group; the second polymer monomer is a multifunctional monomer, which contains at least two unsaturated functional groups, and different types of unsaturated functional groups are not in the same plane, and a plurality of the multifunctional monomers can be polymerized to form a three-dimensional structure; Preferably, the ligand comprises a first ligand and / or a second ligand; The first ligand comprises a modified functional group, and the modified functional group is coordinated to a defect vacancy of the perovskite quantum dot; The second ligand comprises at least two anchoring functional groups, one of which is bonded to the perovskite quantum dot, and the other is bonded to the first polymer monomer or the second polymer monomer.
4. The method for preparing perovskite quantum dots@polymer powder according to claim 3, characterized in that: The first polymer monomer includes any one of methyl acrylate, methyl methacrylate, styrene, and isobornyl acrylate; Preferably, the second polymer monomer comprises any one or a combination of at least two of acrylic acid, acrylic acid ester, perfluorodecene or vinyl pyrrolidone; Preferably, the first ligand comprises any one or a combination of at least two of oleylamine, oleic acid, octylamine, octanoic acid, dodecylbenzenesulfonic acid, didodecylammonium bromide, oleylamine chloride, octylamine bromide, oleylamine bromide or iodinated oleylamine; Preferably, the second ligand comprises any one of hexanedithiol, 3,3'-thiodipropionic acid, trimethylolpropane tris(3-mercaptopropionate) or pentaerythritol tetrakis(3-mercaptopropionate) or a combination of at least two thereof; Preferably, the initiator comprises a photoinitiator and / or a thermal initiator.
5. The method for preparing perovskite quantum dots@polymer powder according to any one of claims 1 to 4, characterized in that: The molar ratio of the B-site ion in the perovskite precursor to the ligand is 1:(0.1-2); Preferably, the molar ratio of the B-site ions in the perovskite precursor to the polymer monomer is 1:(10-50); Preferably, in the perovskite precursor, the molar ratio of the B-site ions to the A-site ions is 1:(0.5-2), and the molar ratio of the B-site ions to the C-site ions is 1:(0.5-10); Preferably, the volume of the solvent corresponding to 1g of polymer monomer is 0.5 to 500mL; Preferably, the reaction solution also includes an antioxidant; Preferably, the molar ratio of the B-site ions in the perovskite precursor to the antioxidant is 1:(0.1-1).
6. The method for preparing perovskite quantum dots@polymer powder according to any one of claims 1 to 5, characterized in that: The spray carrier gas in the spray process includes a protective gas; Preferably, the temperature of the spray carrier gas during the spraying process is 50 to 120°C; Preferably, the light source in the photocuring reaction includes ultraviolet light or blue light; Preferably, the curing power during the photocuring reaction is 50 to 20000 mW / cm 2 .
7. The method for preparing perovskite quantum dots@polymer powder according to any one of claims 1 to 6, characterized in that: After the light curing reaction, heating and drying treatment is carried out under the same light source; Preferably, the heating and drying temperature is 80-120°C.
8. The method for preparing perovskite quantum dots@polymer powder according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: The perovskite precursor, ligand, polymer monomer, initiator and solvent are mixed to obtain a reaction solution, and the reaction solution is sprayed to obtain spray droplets. The temperature of the spray carrier gas during the spraying process is 50 to 120° C. The spray droplets are sprayed at 50 to 20000 mW / cm 2 The curing power is used to perform a photocuring reaction. After the photocuring reaction, a heating and drying treatment is performed at a temperature of 80 to 120° C. under the same light source to obtain the perovskite quantum dot@polymer powder.
9. A perovskite quantum dot@polymer powder, characterized in that: The perovskite quantum dot@polymer powder is prepared by the preparation method according to any one of claims 1 to 8; in the perovskite quantum dot@polymer powder, a plurality of polymer monomers are polymerized to form a plurality of coating cages with three-dimensional shell structures, and the coating cages coat the perovskite quantum dots; The ligand contains at least two groups of functional groups, one group of which is bonded to the inner wall of the coating cage, and the other group of which is bonded to the perovskite quantum dots; the perovskite quantum dots are anchored in the coating cage through the ligand.
10. A use of the perovskite quantum dot@polymer powder as claimed in claim 9, characterized in that: The use includes using perovskite quantum dot@polymer powder in display devices.
Citation Information
Patent Citations
Method for preparing perovskite quantum dot nanorod from methylamine lead bromide perovskite quantum dots
CN107286930A
UV glue, perovskite quantum dot glue solution and perovskite quantum dot packaging structure
CN116694293A